2022
DOI: 10.1039/d2tb01122k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bone regeneration via PHA scaffolds coated with polydopamine-captured BMP2

Abstract: The hierarchical three-dimensional (3D)-printing scaffolds based on microbial polyester poly(3-hydrxoybutyrate-co-4-hydroxybutyrate) (P34HB) were designed and used for bone tissue engineering via surface functionalization on the 3D-printed (P34HB) scaffolds using polydopamine (PDA)-mediated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Currently, PHB/P34HB-BMP2/PDA materials that adhere to PDA under alkaline and aerobic conditions are being designed, resulting in improved osteogenic bioactivity and improved adhesion and proliferation of stem cells with prolonged release for 30 days via a bioactive pathway. 113 Researchers designed a material with mixtures of PHB/PHBHHx/ PLA/PEG, which were implanted subcutaneously in rabbits to evaluate their degradation and tissue reactions. The results of the in vivo tests demonstrated that all the materials tested provoked mild responses in the tissues without inducing any rejection of the material.…”
Section: Studiesmentioning
confidence: 99%
“…Currently, PHB/P34HB-BMP2/PDA materials that adhere to PDA under alkaline and aerobic conditions are being designed, resulting in improved osteogenic bioactivity and improved adhesion and proliferation of stem cells with prolonged release for 30 days via a bioactive pathway. 113 Researchers designed a material with mixtures of PHB/PHBHHx/ PLA/PEG, which were implanted subcutaneously in rabbits to evaluate their degradation and tissue reactions. The results of the in vivo tests demonstrated that all the materials tested provoked mild responses in the tissues without inducing any rejection of the material.…”
Section: Studiesmentioning
confidence: 99%
“…Polymers and inorganic substances that are used to manufacture PHB composites impact the osteogenic properties of scaffolds made of them. For example, polydopamine coating of P4HB copolymer scaffolds manufactured by rapid 3D prototyping allowed to functionalize scaffolds with growth factors such as BMP-2 [ 79 ]. Addition of nanosized hydroxyapatite to scaffolds made of a PHB–keratin composite results in an improvement in the attachment of osteoblast-like cells of the MG-63 line and an increase in the activity of alkaline phosphatase therein [ 76 ].…”
Section: Scaffolds From Poly(3-hydroxybutyrate) and Its Copolymers Fo...mentioning
confidence: 99%
“…Addition of nanosized hydroxyapatite to scaffolds made of a PHB–keratin composite results in an improvement in the attachment of osteoblast-like cells of the MG-63 line and an increase in the activity of alkaline phosphatase therein [ 76 ]. The coating of 3D-printed P4HB scaffolds with polydopamine developed their ability to enhance osteogenic differentiation of MSCs in an osteogenic environment, which was demonstrated by an increase in alkaline phosphatase activity, an increase in calcium salt deposition, and an increase in osteocalcin expression in cells [ 79 ].…”
Section: Scaffolds From Poly(3-hydroxybutyrate) and Its Copolymers Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pure P3HB is considered too brittle for many applications, but its copolymers with monomers such as 4HB, 3HV, and 3HHx have superior mechanical properties compared to pure P3HB homopolymers. These copolymers are also being actively studied in the field of tissue reconstruction [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%